Hubungan antara jarak proyek dengan persepsi masyarakat terhadap pembangunan rumah sakit di Kabupaten Demak - Erma Zakiy Arifah; Trida Ridho Fariz; Andin Irsadi; Abdul Jabbar (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
The social impact of development is assessed in an Environmental Impact Assessment (AMDAL) document, typically using administrative distance buffers based on Government Regulation No. 22 of 2021, Article 44, Paragraph 2. Communities living close to a planned project are expected to experience both benefits and losses, which may be influenced by proximity to the project. This study analyzes how spatial distance or village boundaries affect social impacts, and the relationship between these factors and public perception of development. The research was conducted in RW 02 / RT 02, 03, 04, 05, and 06 in Pulosari Village. The study used four impact indicators: social patterns (S), business opportunities (E), comfort, and public order (B). Data was collected through questionnaires, observations, and purposive random sampling. The results showed that the most significant impact was on social patterns, with 97% of respondents agreeing that development affects social behavior. Perceptions based on project distance were: very close (3.16), close (3.04), far (2.96), and very far (3.44), with "very far" classified as "very high." For road distance, perceptions were: very close (3.08), close (3.92), far (3.24), and very far (3.12), all classified as "high." However, Chi-Square analysis revealed no significant difference between spatial distance and perception. Both project and road distances showed a relationship in terms of strength, but no significant differences were found, likely due to the flat nature of the urban area. The information presented in this research can be developed as a reference for making AMDAL by creating a mathematical model to provide more specific information.